The Signature Amino Acid Residue Serine 31 of HIV-1C Tat Potentiates an Activated Phenotype in Endothelial Cells - Menon, Malini; Budhwar, Roli; Shukla, Rohit Nandan; Bankar, Kiran; Vasudevan, Madavan; Ranga, Udaykumar (Frontiers in Immunology, 2020)
The natural cysteine to serine variation at position 31 of Tat in HIV-1C disrupts the dicysteine motif attenuating the chemokine function of Tat. We ask if there exists a trade-off in terms of a gain of function for HIV-1C Tat due to this natural variation. We constructed two Tat -expression vectors encoding Tat proteins discordant for the serine 31 residue (CS-Tat vs. CC-Tat), expressed the proteins in Jurkat cells under doxycycline control, and performed the whole transcriptome analysis to compare the early events of Tat-induced host gene expression. Our analysis delineated a significant enrichment of pathways and gene ontologies associated with the angiogenic signaling events in CS-Tat stable cells. Subsequently, we validated and compared angiogenic signaling events induced by CS- vs. CC-Tat using human umbilical vein endothelial cells (HUVEC) and the human cerebral microvascular endothelial cell line (hCMEC/D3). CS-Tat significantly enhanced the production of CCL2 from HUVEC and induced an activated phenotype in endothelial cells conferring on them enhanced migration, invasion, and in vitro morphogenesis potential. The ability of CS-Tat to induce the activated phenotype in endothelial cells could be of significance, especially in the context of HIV-associated cardiovascular and neuronal disorders. The findings from the present study are likely to help appreciate the functional significance of the SAR (Signature Amino acid Residues) influencing the unique biological properties.